2000
DOI: 10.2307/2654387
|View full text |Cite
|
Sign up to set email alerts
|

The Proximate Causes of Employment Discrimination

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
352
0
9

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(372 citation statements)
references
References 18 publications
11
352
0
9
Order By: Relevance
“…HR managers did not accept this explicitly, but through the experiences of female employees it was evident that male HR managers practice gender bias at workplace in relation to SH issues. This particular finding is consistent with the previous research which explains the link between managerial decisions and gender discrimination at workplace (Weeden et al 2001;Reskin 2000).…”
Section: Resultssupporting
confidence: 83%
“…HR managers did not accept this explicitly, but through the experiences of female employees it was evident that male HR managers practice gender bias at workplace in relation to SH issues. This particular finding is consistent with the previous research which explains the link between managerial decisions and gender discrimination at workplace (Weeden et al 2001;Reskin 2000).…”
Section: Resultssupporting
confidence: 83%
“…45 . 46 Krieger, 1995;Reskin, 2000. 47 Elvira and Graham, 2002. 48 Stainback, Tomaskovic-Devey, and Skaggs, 2010. 49 Burk and Espinoza, 2012. 50 Irwin Sandler, Sharlene A. Wolchik, Gracelyn Cruden, Nicole E. Mahrer, Soyeon Ahn, Ahnalee Brincks, and C. Hendricks Brown, "Overview of Meta-Analyses of the Prevention of Mental Health, Substance Use, and Conduct Problems," Annual Review of Clinical Psychology, Vol. 10, 2014, pp.…”
Section: Strategies For Preventing Substance Abusementioning
confidence: 99%
“…In addition to the aforementioned selection mechanism, exclusion and social inequality might result from non-intentionally biased cognitive instruments, such as stereotypes (Reskin, 2000). Siniver (2011) showed that immigrant physicians receive lower earnings owing to statistical discrimination in Israel, and Shuval (1995) addressed the negative stereotyping of immigrant physicians' qualifications as a barrier for integration.…”
Section: Integration Vs Horizontal Segregation In the Labour Marketmentioning
confidence: 99%